Two new species of miniature tetras of the fish genus Priocharax from the Rio Juruá drainage, Acre, Brazil (Teleostei: Characiformes: Characidae) - Mattox, George M.T.; Britz, Ralf; Souza, Camila S. [UNESP]; Casas, André L.S.; Lima, Flávio C.T.; Oliveira, Claudio [UNESP] (Canadian Science Publishing, 2023)
Two new miniature tetra species of the Neotropical characid genus Priocharax Weitzman and Vari, 1987 are described, raising the known species diversity to seven. Both species occur in the Rio Juruá system, Cruzeiro do Sul municipality, Acre State, Brazil. Priocharax toledopizae sp. nov. occurs in streams flowing to the lower Rio Moa, a tributary of Rio Juruá, and is distinguished from congeners by a combination of presence of claustrum and infraorbitals 1 and 2, absence of infraorbital 3, and presence of five branched pelvic-fin rays. Priocharax marupiara sp. nov. is known from Igarapé Canela Fina, tributary of Rio Juruá, and is diagnosed by a combination of fewer maxillary teeth (21–27 vs. 27–58 in remaining species), fewer branched anal-fin rays (18–23 vs. 22–27 in two species) and colour pattern. Both species differ from each other in the general body shape: Priocharax toledopizae is more robust with deep body and Priocharax marupiara more elongate. DNA barcode data support the specific distinctness of the two new species and that of the other five species in the genus. We describe a remarkable sexual dimorphism of the pelvic girdle of Priocharax toledopizae in which the pelvic musculature is enlarged forming a pedicel for the fin in mature males. Most localities where these species were found suffer from significant degradation mainly due to litter accumulation and suppression of the riparian forest, raising concerns about their conservation status.
Keywords: anatomy; DNA barcode; integrative taxonomy; miniature tetra; Neotropics; systematics